Fikih Digital Milenial: Sistem Gacha Pada Game Online Efootball Champion Squads - Al Ayyubie, Bahaestie (Program Studi Hukum Ekonomi Syariah, 2023)
In fulfilling their life needs, humans have relationships with other humans. Included in this is fulfilling entertainment needs. One of the means to fulfill entertainment needs in the current era is online games and many online games use the gacha system which is questionable in Islam. This research uses qualitative methods based on reality in the field. Primary data for this research was obtained from interviews with eFootball Champion Squads Game players. Secondary data was obtained from books and other sources related to this research. The data obtained from the field is then examined and analyzed and conclusions are drawn. The result of this research is that the gacha system used in the eFootball Champion Squads Game to obtain items violates the provisions of Islamic law because there are elements of gharar and maisir in obtaining items in the eFootball Champion Squads Game. In getting items, eFootball Champion Squads Game players have to determine their fate by participating in the game and the number and type of items they get are uncertain so players feel disadvantaged.